Nuttalliella namaqua Bedford, 1931, a sole extant species of the genus Nuttalliella – a scoping review - Ledwaba, Maphuti Betty; Malatji, Dikeledi Petunia (Frontiers in Parasitology, 2024)
is the sole extant tick species that belongs to the genus and family Nuttalliella and Nuttalliellidae respectively. With the characteristics that are respectively distinctive to hard and soft ticks, it is regarded as the species closest to the ancestral lineage of ticks as well as the missing link between the Argasidae and Ixodidae families. In this review, literature search of the articles reporting on N. namaqua was done in Google Scholar and PubMed databases. After relevance and eligibility screening, 12 articles were deemed eligible and appraised. The results showed that N. namaqua was respectively distinct to limited regions of Africa such as Botswana, Namibia, Mozambique, South Africa and Tanzania. The review also indicated that N. namaqua was collected from murid rodents, African Savanna hare, scrub hare, elephant shrews, rock hyraxes, black backed jackal, lizards and off-host in locations that include under a stone, rock crevices, on a rock wall and respectively in the nests of an eagle and a lesser striped swallow. Irrespective of all the reports, natural hosts of the nymphs are still not clearly defined. Numerous phylogeny studies have reported Nuttalliellidae as the sister-lineage to Argasidae and Ixodidae tick families. Moreover, a recent report indicated that the similarities between Nuttalliellidae and the fossil families Deinocrotonidae and Legionaris award them to be merged into one family, preferably Nuttalliellidae Thus, further research on this family, will perhaps provide more knowledge about its unclear distribution, life cycle as well as the evolution of ticks in general.